2023
DOI: 10.1088/1361-6595/acf8ef
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic confinement less microwave discharge gridded ion thruster

Ming Zeng,
Hui Liu,
Hongyan Huang
et al.

Abstract: A watt-level microwave discharge is induced without magnetic confinement for a high-precision gridded ion thruster, making use of a coaxial transmission line resonator. The thruster is characterized by performance measurements and plasma diagnosis, and a description of the operating mechanism of this thruster is given in this paper. A Faraday probe and a retarding potential analyzer are employed for the diagnosis. The results show that the plume divergence increases due to the electric field formed between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…An important advantage of MW discharges is the possibility of electrodeless energy deposition to the plasma at a relatively low electron temperature. One of the modern areas of experimental research is the use of electrodeless MW discharges in rocket engines [17,18], plasma engines [19,20], and aerodynamic applications [21][22][23][24][25][26][27][28][29]. In particular, experimental studies have shown high efficiency of such discharges from the point of view of energy deposition to supersonic and hypersonic flows for the flow control and drag reduction near aircraft moving in the atmosphere [21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…An important advantage of MW discharges is the possibility of electrodeless energy deposition to the plasma at a relatively low electron temperature. One of the modern areas of experimental research is the use of electrodeless MW discharges in rocket engines [17,18], plasma engines [19,20], and aerodynamic applications [21][22][23][24][25][26][27][28][29]. In particular, experimental studies have shown high efficiency of such discharges from the point of view of energy deposition to supersonic and hypersonic flows for the flow control and drag reduction near aircraft moving in the atmosphere [21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%